The origins and influence of victim assistance: Contributions of the Mine Ban Treaty, Convention on the Rights of Persons with Disabilities and Convention on Cluster Munitions. (April 2023) - Docherty, Bonnie; Sanders-Zakre, Alicia
Abstract: The establishment of victim assistance as a core element of humanitarian disarmament emerged from three treaties: the 1997 Mine Ban Treaty (MBT), the 2006 Convention on the Rights of Persons with Disabilities (CRPD) and the 2008 Convention on Cluster Munitions (CCM). The MBT introduced the concept of victim assistance, and the CPRD created a framework of human rights that influenced its evolution. Drawing on its predecessors, the CCM made victim assistance a robust and rights-based legal obligation. This article analyses the negotiating history and content of the treaties to show how victim assistance evolved, particularly in the areas of inclusion and human rights. It examines the treaties' implementation, which reveals that while the CRPD set standards for victim assistance, the MBT and CCM's victim assistance programmes have benefitted persons with disabilities in practice. Finally, it offers lessons from the MBT, CRPD and CCM for implementation and interpretation of victim assistance obligations under the 2017 Treaty on the Prohibition of Nuclear Weapons. The article concludes that the three treaties have collectively established assisting victims as a feature of disarmament law, helped persons with disabilities realize their rights, and laid the groundwork for adapting victim assistance to new challenges.